Immunity, Inflammation and Heart Failure: Their Role on Cardiac Function and Iron Status - Perticone, Maria; Zito, Roberta; Miceli, Sofia; Pinto, Angelina; Suraci, Edoardo; Greco, Marta; Gigliotti, Simona; Hribal, Marta Letizia; Corrao, Salvatore; Sesti, Giorgio; Perticone, Francesco (Frontiers in Immunology, 2019)
Aims: Heart failure is a clinical syndrome characterized by subclinical systemic inflammation and immune system activation associated with iron deficiency. No data exist on the various activations of immune-mediated mechanisms of inflammation in heart failure patients with reduced/preserved ejection fraction. We aimed to (1) investigate possible differences in inflammatory parameters and oxidative stress, and (2) detect a different iron status between groups. Materials and Methods: We enrolled 50 consecutive Caucasian outpatients with heart failure. All patients underwent echocardiographic measurements, laboratory determinations, evaluation of iron status and Toll-like receptors, and NF-κB expression in peripheral blood mononuclear cells, as well as pro-inflammatory cytokines. All statistical calculations were made using SPSS for Mac version 21.0. Results: Patients with reduced ejection fraction showed significantly lower hemoglobin levels (12.3 ± 1.4 vs. 13.6 ± 1.4 g/dl), serum iron (61.4 ± 18.3 vs. 93.7 ± 33.7 mcg/dl), transferrin iron binding capacity (20.7 ± 8.4 vs. 31.1 ± 15.6 %), and e-GFR values (78.1 ± 36.1 vs. 118.1 ± 33.9 ml/min/1.73 m2) in comparison to patients with preserved ejection fraction, while unsaturated iron binding capacity (272.6 ± 74.9 vs. 221.7 ± 61.4 mcg/dl), hepcidin (4.61 ± 0.89 vs. 3.28 ± 0.69 ng/ml), and creatinine (1.34 ± 0.55 vs. 1.03 ± 0.25 mg/dl) were significantly higher in the same group. When considering inflammatory parameters, patients with reduced ejection fraction showed significantly higher expression of both Toll-like receptors-2 (1.90 ± 0.97 vs. 1.25 ± 0.76 MFI) and Toll-like receptors-4 (4.54 ± 1.32 vs. 3.38 ± 1.62 MFI), respectively, as well as a significantly higher activity of NF-κB (2.67 ± 0.60 vs. 1.07 ± 0.30). Furthermore, pro-inflammatory cytokines, interleukin-1, and interleukin-6, was significantly higher in patients with reduced ejection fraction, while the protective cytokine interleukin-10 was significantly lower in the same group. Correlational analyses demonstrated a significant and inverse relationship between left ventricular function and inflammatory parameters in patients with reduced ejection fraction, as well as a direct correlation between ferritin and inflammatory parameters. Conclusions: Our data demonstrate a different immune-mediated inflammatory burden in heart failure patients with reduced or preserved ejection fraction, as well as significant differences in iron status. These data contribute to further elucidate pathophysiologic mechanisms leading to cardiac dysfunction.